Gambaran Angka Drop Out Pada Penggunaan Terapirumatan Metadon Di Puskesmas Senen, Puskesmas Gambir Dan Puskesmas Kemayoran Jakarta Pusat Pada Tahun 2014-2016 Dan Tinjauannya Menurut Islam - Ichwan, Zulha Annisa; Poerwantoro, Bambang; Zuhroni, Zuhroni (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2018)
Currently Indonesia has a drug emergency status. Drug users in Indonesia was recorded as many as 5.1 million people. Every year, about 15 thousand people die from drug use. To overcome all these circumstances the government through the Regulation of the Minister of Health, apply Methadone Maintenance Therapy program. Methadone is not a cure for opiate dependency: during methadone use, the user remains dependent on opiates physically. Participants of methadone maintenance therapy often feel themselves healthy enough to get out of the therapy program (drop out). This study aims to determine the number of dropout in the use of methadone maintenance therapy at Puskesmas Senen, Puskesmas Gambir and Puskesmas Kemayoran Central Jakarta from 2014 to 2016 and overview in Islamic views. Method: This research method used descriptive survey with retrospective data using secondary data in the form of data Drop Out on Methadone Usage at Puskesmas Senen, Puskesmas Gambir and Puskesmas Kemayoran Central Jakarta in 2014-2016. Result: The results of this study indicate the number of patients dropped out on methadone maintenance therapy at Puskesmas Senen, Puskesmas Gambir and Puskesmas Kemayoran in 3 years. At Puskesmas Senen, the highest drop out rate occurred in 2015 with 16 patients from 239 registered patients (6.7%). At Puskesmas Gambir, the highest drop out rate occurred in 2015 with 34 patients from 98 registered patients (34.7%). And at Puskesmas Kemayoran, the highest drop out rate occurred in 2015 with 11 patients from 55 patients who registered (20%). Patients dropping out on methadone maintenance therapy in both Puskesmas Senen and Kemayoran were mostly male and most dropped out at 25 to 49 years with 24 patients out of 25 drop out patients (96%). Conclusion: The highest drop out rate in all three puskesmas occurred in 2015. Patients drop out most of the male and most occur in the age group of 25-49 years. In the view of Islam drug abuse is illegal but if used for medical purposes and not excessive is allowed. This is a state of emergency and the circumstances are still allowed to remember the method often raised by scholars,